Bias-free photoelectrochemical water splitting with photosystem II on a dye-sensitized photoanode wired to hydrogenase. (November 2018) - Sokol, Katarzyna; Robinson, William; Warnan, Julien; Kornienko, Nikolay; Nowaczyk, Marc; Ruff, Adrian; Zhang, Jenny; Reisner, Erwin
Abstract Natural photosynthesis stores sunlight in chemical energy carriers, but it has not evolved for the efficient synthesis of fuels, such as H2 . Semi-artificial photosynthesis combines the strengths of natural photosynthesis with synthetic chemistry and materials science to develop model systems that overcome nature's limitations, such as low-yielding metabolic pathways and non-complementary light absorption by photosystems I and II. Here, we report a bias-free semi-artificial tandem platform that wires photosystem II to hydrogenase for overall water splitting. This photoelectrochemical cell integrated the red and blue light-absorber photosystem II with a green light-absorbing diketopyrrolopyrrole dye-sensitized TiO2 photoanode, and so enabled complementary panchromatic solar light absorption. Effective electronic communication at the enzyme–material interface was engineered using an osmium-complex-modified redox polymer on a hierarchically structured TiO2 . This system provides a design protocol for bias-free semi-artificial Z schemes in vitro and provides an extended toolbox of biotic and abiotic components to re-engineer photosynthetic pathways. Semi-artificial photosynthetic systems combine natural and synthetic features to overcome limitations of each approach to produce solar fuels. Sokol et al. integrate a dye-sensitized TiO2 photoanode with the natural machineries, photosystem II and hydrogenase, to split water without additional applied bias.